Concussion assessment and management - Hunt, T.; Asplund, C. (Clinics in Sports Medicine, 2010)
Sport-related concussions are becoming common place in athletics and daily activity. Proper assessment and management of concussions are crucial, as repeat concussion can result in prolonged symptoms and catastrophic outcomes. New research is changing the way concussions are managed. The previously used systems have been abandoned in favor of individualized assessment and management using a multidisciplinary approach to include clinical signs, neuropsychological assessment, and postural stability. Transitioning the new evidence to clinical practice is the future of diagnosis, management, and safe return to play following sport-related concussions. This article aims to bridge this gap and provide a systematic, easy-to-use methodology in the management of sport-related concussions.